Linguliform microbrachiopods from Las Aguaditas and Las Chacritas Formations (Middle-Upper Ordovician) of Argentine Precordillera - Lavié, Fernando Julián (2019)
Middle-Upper Ordovician linguliform microbrachiopods are described and illustrated for the first time from the Las Aguaditas Formation at the Los Blanquitos and Mogotes Azules ranges and from the Las Chacritas Formation at the Las Chacritas River section, Central Argentine Precordillera. This systematic study includes nine families, namely Obolidae, Paterulidae, Discinidae, Acrotretidae, Scaphelasmatidae, Torynelasmatidae, Ephippelasmatidae, Biernatidae and Eoconulidae. This diverse fauna is conformed of specimens corresponding to Lingulops sp., Paterula incognita Mergl, Schizotreta sp., Scaphelasma zharykensis Popov, Torynelasma? sp., Akmolina sp., Ephippelasma sp., Numericoma simplex Holmer, and Eoconulus sp. However, specimens from the order Acrotretida proved to be an important component of this fauna, enabling the recognition of two new species which are thoroughly described, Conotreta andina n. sp. and Biernatia rhapsody n. sp.